2004
DOI: 10.1038/sj.mp.4001388
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of bipolar affective disorder on chromosome 8q24: follow-up and parametric analysis

Abstract: Our group first reported a linkage finding for bipolar (BP) disorder on chromosome 8q24 in a study of 50 multiplex pedigrees, with an HLOD score reaching 2.39. Recently, Cichon et al reported an LOD score of 3.62 in the same region using two-point parametric analysis. Subsequently, we published the results of a genome scan for linkage to BP disorder using a sample extended to 65 pedigrees in which chromosome 8q24 provided the best finding, an NPL score of 3.13, approaching the accepted score for suggestive lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 43 publications
(51 reference statements)
3
35
1
1
Order By: Relevance
“…However, some of the most significant results in the NIMH sample did not replicate in the German sample, and by design, we did not pursue association signals present only in the German sample. Association signals that did not replicate under our criteria were observed in several genes that have been implicated by previous studies, [50][51][52][53] including NPAS3, GRIK2, GRM3, GRM4, KCNQ3 and GRIN2B (data not shown). Since others may wish to pursue these findings, we will make our genome-wide set of results available at http://mapgenetics.nimh.nih.gov/bp_pooling.…”
Section: Ae Baum Et Almentioning
confidence: 51%
“…However, some of the most significant results in the NIMH sample did not replicate in the German sample, and by design, we did not pursue association signals present only in the German sample. Association signals that did not replicate under our criteria were observed in several genes that have been implicated by previous studies, [50][51][52][53] including NPAS3, GRIK2, GRM3, GRM4, KCNQ3 and GRIN2B (data not shown). Since others may wish to pursue these findings, we will make our genome-wide set of results available at http://mapgenetics.nimh.nih.gov/bp_pooling.…”
Section: Ae Baum Et Almentioning
confidence: 51%
“…27 Interestingly, a susceptibility locus for BD was recently identified on chromosome 8q24, a region that contains the KCNQ3 gene. 39 We tested the effects of Q2-3H2 or Q2-3H9 on KCNQ3 channel activity and we found that currents generated by the channel are unchanged in the presence of either of the splice variants (Supplementary information, Figure 7). These data indicate that these proteins probably do not interact.…”
Section: Pp2a-bc and Kcnq2 In Bipolar Diseasementioning
confidence: 99%
“…[5][6][7] Increased OPG serum levels have been reported to be significantly related to cardiovascular disease (CVD) phenotypes, 8 and in apparently healthy individuals, with an increased future risk of coronary events. 9 Genetic variation at the human OPG gene locus has been associated with colorectal 10 /prostate cancer risk 11 and bipolar disorders 12 in whole genome approaches; in single variant analyses, OPG T-159C has been associated with elevated OPG serum levels, 13 CVD, 13,14 intima media thickness, and reduced maximal forearm blood flow in healthy subjects. 15 The human OPG gene (8q24) consists of 5 exons and 4 introns, and is transcribed into 4 transcripts (2.4 kb, 3.0 kb, 4.2 kb, and 6.5 kb in lengths).…”
mentioning
confidence: 99%